Cryogenic gaseous photomultipliers and liquid hole- multipliers: advances in THGEM-based sensors for future noble-liquid TPCs. (October 2015) - Arazi, L; Coimbra, A E C; Erdal, E; Israelashvili, I; Rappaport, M L; Shchemelinin, S; Vartsky, D; dos Santos, J M F; A, Breskin
Abstract: Dual-phase noble-liquid TPCs are presently the most sensitive instruments for direct dark matter detection. Scaling up existing ton-scale designs to the multi-ton regime may prove to be technologically challenging. This includes both large-area coverage with affordable high-QE UV-photon detectors, and maintaining high precision in measuring the charge and light signals of rare events with keV-scale energy depositions. We present our recent advances in two complementary approaches to these problems: large-area cryogenic gaseous photomultipliers (GPM) for UV-photon detection, and liquid-hole multipliers (LHM) that provide electroluminescence light in response to ionization electrons and primary scintillation photons, using perforated electrodes immersed within the noble liquid. Results from a 10 cm diameter GPM coupled to a dual-phase liquid- xenon TPC demonstrate the feasibility of recording - for the first time - both primary ("S1") and secondary ("S2") scintillation signals, over a very broad dynamic range. The detector, comprising a triple-THGEM structure with CsI on the first element, has been operating stably at 180 K with gains larger than 10 5 ; it provided high single-photon detection efficiency - in the presence of massive alpha-particle induced S2 signals; S1 scintillation signals were recorded with time resolutions of 1.2 ns (RMS). Results with the LHM operated in liquid xenon yielded large photon gains, with a pulse-height resolution of 11% (RMS) for alpha-particle induced S2 signals. The detector response was stable over several months. The response of the S2 signals to rapid changes in pressure lead to the conclusion that the underlying mechanism for S2 light is electroluminescence in xenon bubbles trapped below the immersed THGEM electrode. Both studies have the potential of paving the way towards new designs of dual- and single-phase noble-liquid TPCs that could simplify the conception of future multi-ton detectors of dark matter and other rare events.